Do we always consistently define the clinically important echocardiographic parameters? - Meluzin, Jaroslav; Gregorova, Zdenka; Podrouzkova, Helena; Panovsky, Roman (Biomedical papers, 2014)
Aims: The aim of this short communication is to highlight some inconsistencies in defining two clinically important echocardiographic parameters with possible impact on clinical practice.Methods and Results: A surview of publications in reputable cardiological journals revealed inconsistencies posing questions on the validity of the published data and on the scrupulousness of the reviewing process. We demonstrate examples of inconsistencies in the calculation of left ventricular mass using Devereux's formula and in the definition of relative wall thickness, two echocardiographic parameters commonly utilized in a clinical practice.Conclusion: It is desirable to follow exactly the definitions of more complex parameters and to unify ways of presenting those with several definitions.
Keywords: left ventricular mass; relative wall thickness